2017
DOI: 10.4103/jehp.jehp_101_15
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of urban Gujarati type 2 diabetics: Prevalence and impact on disease control

Abstract: CONTEXT:Type 2 diabetes is the modern epidemic wherein patient care needs multiple approaches, education, and self-awareness being one of them. There are some knowledge, attitude, and practice (KAP) studies from India but very few relating it with disease control.AIMS:We tried to study KAP of treated type 2 diabetics and its correlation with glycemic control.SETTINGS AND DESIGN:Cross-sectional KAP study.SUBJECTS AND METHODS:We formulated KAP questionnaires in the form of KAP - 10 points for each and total 30. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 24 publications
3
15
1
1
Order By: Relevance
“…We found that the determinants of better diabetes knowledge were higher education levels, younger age, and higher monthly income. Similar findings were reported by other studies in China, India, Kuwait, Jordan, and Costa Rica [13,15,17,20,31]. The elderly and less-educated patients may have had lower knowledge test scores because of deep-rooted misconceptions about diabetes ingrained years ago or perhaps because of difficulty understanding health education materials or newer information.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We found that the determinants of better diabetes knowledge were higher education levels, younger age, and higher monthly income. Similar findings were reported by other studies in China, India, Kuwait, Jordan, and Costa Rica [13,15,17,20,31]. The elderly and less-educated patients may have had lower knowledge test scores because of deep-rooted misconceptions about diabetes ingrained years ago or perhaps because of difficulty understanding health education materials or newer information.…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, lack of awareness and insufficient understanding of diabetes could lead to adverse consequences. In recent years, a few studies have investigated patients' knowledge about their diabetes [7][8][9][10] or examined the association between diabetesrelated self-care knowledge and glycemic control [10][11][12][13]. For example, a study conducted by Mann et al demonstrated that certain misconceptions about diabetes and its treatment were associated with poor glycemic control [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results related to the level of a patient's knowledge on diabetes were varies. A study by Solanki, Sheth, Shah, & Mehta (2017) revealed that the patients were unaware of their insulin level, which may have led to misinterpretation the insulin as harmful. The authors further found that patients believed diabetes can be cured, and more than half of the patients considered diabetes to be curable by consuming bitter food.…”
Section: Informationmentioning
confidence: 99%
“…La desinformación representaría un predictor de complicaciones y de mortalidad por DM2 al asociarse a una adherencia deficiente [4] ; así es como se ha reconocido en diversos estudios que la educación para el autocuidado es un pilar fundamental dentro del manejo del paciente que padece de esta enfermedad [5] y, dado que de la misma se derivan actitudes y prácticas que influyen de manera positiva en la evolución de la enfermedad, se hace indispensable evaluar si medidas que pueden generar intervenciones educativas, como el conocimiento de la enfermedad, pueden influir en mejorar la adherencia, controlar la enfermedad y disminuir la carga que se produce. En nuestro país, un estudio que evaluó los conocimientos que tiene los diabéticos sobre su padecimiento [6] mostró cifras y datos alarmantes que plantean la necesidad de desarrollar y fortalecer medidas educativas.…”
Section: Introductionunclassified